Upaya Pemerintah Daerah dalam Mereduksi Eksploitasi Ekonomi Anak (Studi pada Perlindungan Anak di Kota Malang) - Akbariah, Laily (Jurnal Administrasi Publik, 2013)
Abstract: The Efforts of Local Government to Reduce of Child Economic Exploitation (A Study of Child Protection in Malang City). The government of Malang City has implemented Kota Layak Anak (KLA) policy. The background of this research was efforts of the government to reduce of child economic exploitation through policies and programs related to child protection must be redefined within the perspective of the effectiveness policy implementation and political will. The efforts to reduce child economic exploitation are not giving significant impact. Implementation of KLA policy does not focus at Cluster V No. 28. The government of Malang City has not constructed child protection policy through KLA from relation level to societal level. It is because the political will of the government of Malang City is only limited to political want. Whereas the role of NGO have great impact and contribution to the protection and welfare of the economically exploited children. Keywords: child protection, child economic exploitation Abstrak: Peran Pemerintah Daerah dalam Mereduksi Eksploitasi Ekonomi Anak. (Studi pada Perlindungan Anak di Kota Malang). Pemerintah Kota Malang telah melaksanakan Kebijakan Kota Layak Anak (KLA). Latar belakang penelitian untuk menyoroti kembali pelaksanaan upaya mereduksi eksploitasi ekonomi anak melalui kebijakan dan program aksi perlindungan anak di Kota Malang dengan mengacu perspektif efektifitas implementasi kebijakan dan political will. Upaya mereduksi eksploitasi ekonomi anak belum memberikan dampak signifikan. Pelaksanaan kebijakan KLA belum terfokus pada Cluster V No. 28. Pemerintah Kota Malang belum mampu mengkontruksikan kebijakan perlindungan anak, melalui KLA pada relation level hingga societal level. Sebab political will Pemerintah Kota Malang masih sebatas political want. Sedangkan peran NGO memiliki kontribusi besar terhadap perlindungan dan kesejahteraan anak yang tereksploitasi ekonomi. Kata kunci: perlindungan anak, eksploitasi ekonomi anak